Perancangan Sistem Informasi Inventory Obat Berbasis Web Pada Apotek Fadhilah Farma - Lusiana, Erda; Imilda; Salam, Abdus (Jurnal Sistem Komputer (SISKOM), 2024)
This research aims to design a Web-Based Drug Inventory Information System at the Fadhilah Farma Pharmacy. In the era of information technology development, the use of reliable information systems has become an important requirement for health institutions such as pharmacies. This research uses the Rapid Application Development (RAD) method to produce efficient and flexible software prototypes. The system development process involves the stages of planning, analysis, design, and maintenance. Data collection methods used include interviews, observation, and literature study. Data analysis is carried out to produce conclusions and recommendations that support decision making in application design. The results of this research are expected to increase the operational efficiency of the Fadhilah Farma Pharmacy, reduce losses due to expired medicines, and improve the quality of service to customers.